PENGAWASAN PELAKSANAAN ANGGARAN OLEH DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN ROKAN HULU TAHUN 2014 - ", Anisah; Tinov, M.Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Provincial Legislative Council (DPRD) as the representative body of the people have an obligation to provide services to the people or the public, so that every policy issued is a means of democracy and mutual communication between the regional head of the community. However, the role and functions of parliament in Rokan Hulu as legislators still not up, especially in the functioning of the budget. This can be seen from the budget absorbed since the year 2010 - 2014 in which the budget endorsed by Parliament Rokan Hulu is only absorbed between 80.4% and 92.31%. This shows that the absorption of the regional budget in Rokan Hulu still not up and need to get serious attention of the parties concerned in view of the value of the budget should have been in accordance with the needs of the budget required in Rokan Hulu. This research was conducted in the Office of the Regional Representatives Council (DPRD) Rokan Hulu. The purpose of this study was to determine the Budget Implementation Oversight by the Regional Representatives Council (DPRD) Rokan Hulu 2014 and to identify constraints in the Budget Implementation Oversight by the Regional Representatives Council (DPRD) Rokan Hulu 2014. The type of data used in this study was composed of primary data and secondary data with the number of informants as many as 8 people. Intake of informants by using purposive sampling technique. The analysis of the data used in this study is a qualitative descriptive way. Based on the results of research conducted by the author can be concluded that the Monitoring the Implementation of the Budget by the House of Representatives (DPRD) Rokan Hulu 2014 conducted through three stages of surveillance, as follows: a) Control of On Stage Planning, b) Monitoring the Implementation Phase and c ) Monitoring in Phase Accountability. Obstacles In Implementation Oversight Budget By Provincial Legislative Council (DPRD) Rokan Hulu 2014 was influenced by two factors: a) Internal factors which include lack of knowledge about governance and lack of expertise legislators particular field which becomes the object of supervision, b ) External factors.Keywords: Oversight, Budget, House of Representatives (DPRD)